How individual differences influence employees' experiences of major organisational change in a large UK insurance company - Seery, Georgina (Cranfield University, 2002)
This thesis examines employees' experiences of major organisational change, with an emphasis upon examining how the personality traits Neuroticism and Extraversion, and the personality disposition Work Locus of Control, influence these experiences. The perspective of employees, who are the main recipients of major change initiatives, is not well represented in the literature. Also, despite calls for research that addresses process and context, existing literature on the role of individual differences in relation to organisational change tends to be aprocessual and acontextual. The present research seeks to overcome these shortcomings by adopting a longitudinal, real-time, qualitative approach. The research elicited employees' perceptions of change as a major change programme unfolded, and examined emerging patterns of employees' experiences in relation to contextual and individual difference factors. The research presents a picture of organisational change as unpredictable and emergent. The research findings demonstrate that employees' experiences of change are varied and suggest that these experiences are influenced by many factors at the personal, group and organisational levels. The research shows that a change 'event' will elicit different types of feelings and responses from the same individual over time, as the event unfolds. Patterns of experience were found which suggested that personality factors, and combinations of these factors, influenced the way aspects of change were perceived by employees, and these perceptions appeared to influence employees' responses to change. The present research contributes towards the change management literature by confirming the view that change is 'messy', emergent and unpredictable, and by presenting evidence to show how employees contribute towards the emergent nature of this process. The research contributes towards the work psychology literature by adopting an approach that contextualises research participants' responses, and presents an account of change as an unfolding process. By focusing upon perceptions, the research is able to offer explanations of how individual differences might influence employees' experiences of major organisational change.